A Philosophical and Historical Analysis of “Generation Identity”: Fascism, Online Media, and the European New Right - Richards, Imogen (Terrorism and political violence, 2022)
This article analyzes ideological and organizational characteristics of the pan-European youth movement, “Generation Identity” (GI), through a philosophical and historical lens. With a synoptic perspective on existing and original research, it outlines an analysis of key GI literature as well as its ideological influences, activist behavior, and media strategies. This research reveals that, like other twentieth and twenty-first century examples of neo-fascism, the movement is syncretic and attempts to legitimize its political aims through reference to historical quasi- and proto-fascist cases, in combination with popular left and right-wing political ideals. A reflection on GI’s activist behavior, on the other hand, demonstrates that the movement is relatively unique in the field of current far-right politics; particularly in the extent to which it draws practical inspiration from the tactics and propagandizing strategies of contemporary left-wing movements. GI’s online presence, including its leaders’ promotion of gamification, also illustrates its distinctive appeal to young, relatively affluent, countercultural and digitally literate populations. Finally, while in many respects GI is characteristic of the “European New Right” (ENR), the analysis finds that its spokespersons’ various promotion of capitalism and commodification, including through their advocacy of international trade and sale of merchandise, diverges from the anti-capitalist philosophizing of contemporary ENR thinkers.